MANAGING INDONESIAN DATA BREACH NOTIFICATION IN THE FINANCIAL SERVICES SECTOR: A CASE FOR ONE-STOP NOTIFICATION MODEL - Algamar, Muhammad Deckri; Munir, Abu Bakar; Hendro (Bank Indonesia, 2024)
As a business of trust, the banking and financial services industry must protect its reputation to ensure consumer’s confidence. However, recent adoption of emerging internet communication technologies (ICT) have introduced new risks and challenges, such as safeguarding systems from cyberattacks and protecting consumer’s personal data. Cyberattacks, especially ransomware have shed new light on the importance of privacy and security throughout the banking and financial industry’s digitization efforts. Any organisation affected by cybersecurity attacks must face a twofold legal question. First, whether or not there has been a violation of the legal security requirements? Second, is to determine whether the attack triggers Data Breach Notification to the Data Protection Authority and/or Data Owners. This paper examines the complexity of maintaining security obligations under Indonesian Law (UU ITE, UU PDP, RPP PDP, and other relevant regulations) while also highlighting the common challenges in steering Data Breach Notification, with an enhanced perspective of the European General Data Protection Regulation (EU GDPR) practices. To address the challenges of patchwork data breach notification requirements in Indonesia, this paper proposes a proactive approach by Indonesia’s future Personal Data Protection Authority in creating a one-stop notification model to enable effective data breach incident management and notification.